The Effect of Water Quality Sources on Concrete Mix Parameters - Abdulrahman A. Salim; Ahmed AL-azzawi (Genius Journals, 2022)
This research investigated the impact of water from various sources on the mechanical characteristics of concrete. The qualities of concrete made with surface water, well water, and tap water are evaluated in this study. The features of concrete specimens with mix ratios of 1:2:4 created with water from various sources were evaluated using compressive strength and density. Concrete specimens made using tap water had the highest mean compressive strength at 90 days, according to the findings. Although well water had the lowest compressive strength, it was determined that it was not acceptable for concrete work, despite the fact that it is currently being utilized on some locations where tap water is unavailable.
Keywords: Water; Concrete; Compressive strength; Tensile strength